2009
DOI: 10.1016/j.cej.2009.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal synthesis of vanadium phosphate catalysts for n-butane oxidation

Abstract: a b s t r a c tIn this paper, we have developed a simple, low-cost, template-free and surfactant-free solvothermal process for synthesis of vanadyl hydrogen phosphate hemihydrate (VOHPO 4 ·0.5H 2 O) with well defined crystal size. The synthesis was performed by reaction of VPO 4 ·2H 2 O with an aliphatic alcohol (isobutyl alcohol, 1-pentanol, 1-hexanol, 1-heptanol or 1-decanol). This afforded well crystallized VOHPO 4 ·0.5H 2 O by solvothermal methods at 120 • C temperature. This new method significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The alcohol plays a role in establishing the morphology of the vanadyl hydrogen phosphate hydrate which, since the transformation to the final catalyst is topotactic, controls the morphology of the final catalyst [8]. We have recently reported a high-pressure solvothermal process to synthesise high crystalline catalyst precursor, VOHPO 4 ·0.5H 2 O [11,14]. It was found that the alcohol used as a reducing agent can control the morphology and the best results are obtained using primary alcohols.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The alcohol plays a role in establishing the morphology of the vanadyl hydrogen phosphate hydrate which, since the transformation to the final catalyst is topotactic, controls the morphology of the final catalyst [8]. We have recently reported a high-pressure solvothermal process to synthesise high crystalline catalyst precursor, VOHPO 4 ·0.5H 2 O [11,14]. It was found that the alcohol used as a reducing agent can control the morphology and the best results are obtained using primary alcohols.…”
Section: Introductionmentioning
confidence: 94%
“…Initial catalyst preparations [9] used water as solvent but most studies, in recent years, have concentrated on the use of alcohols as they can exhibit the duel role of solvent and reducing agent. In previous studies [10][11][12][13] we have shown that very active catalysts can be prepared using an organic (VPO) and dihydrate (VPD) method. The alcohol plays a role in establishing the morphology of the vanadyl hydrogen phosphate hydrate which, since the transformation to the final catalyst is topotactic, controls the morphology of the final catalyst [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several more of the indexed peaks matched that of oxovanadium phosphate dihydrate from the database (ICDD:98-020-0884) (Tietze, 1981). However, the peak with the highest intensity at 2θ = 12.3 • corresponds to V 2 O 5 phase (Rownaghi et al, 2009). Peaks of significant intensity that corresponds to VOPO 4 and VOHPO 4 .2H 2 O were identified in the XRD pattern of VOP2.…”
Section: Resultsmentioning
confidence: 79%
“…The crystallite size was inversely proportional to the BET surface area, in which a large crystallite size could reduce the surface area of the catalyst. 26 Moreover, the CuO/CaO(10 : 90)(ES) catalyst calcined at 700 C recorded the highest crystallite size of CaO (55.24 nm), CuO (41.91 nm) and CaCuO 2 (41.81 nm), followed by the crystallite size of the ZnO/CaO(10 : 90)(ES) catalyst calcined at Overall, the micrographs showed an irregular shape with varied particle size on the surface of the catalysts. Based on the FESEM micrograph in Fig.…”
Section: Properties Of the Rened Waste Cooking Oil And Biodiesel Productmentioning
confidence: 99%